DEVELOP PEDAGOGICAL THINKING IN THE EDUCATIONAL PROCESS - Ergashev Jakhongir Mamanazarovich (Uzbekistan Open Conference, 2025)
One of the initial principles of the work is considered to be the teacher themselves, a particularly important means of education, for they are not simply a bearer of knowledge; they invite students to utilize themselves, their knowledge, experience, their views, with which they may disagree, etc.; they offer students their willingness to provide the means for advancement and knowledge and to help students find these means themselves.
Keywords: competence; formation; education; interactive; methods